(untitled) (International Journal of Food and Nutritional Sciences, 2019)
Expansion of Engineering Colleges (2008): The All-India Council of Technical Education (AICTE) allowed numerous societies, academies, or trusts to establish engineering colleges across India in 2008. This led to a proliferation of engineering institutions.